DINAMIKA KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBINA BUDAYA ORGANISASI DI LEMBAGA PENDIDIKAN ISLAM - Mukhlisin Mukhlisin; Nurrahmaniah Nurrahmaniah; Rokimin Rokimin; Miftah Hur Rahman ZH; Zahid Zufar At Thaariq (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to explore the principal's efforts in fostering organizational culture at MTs Darunnajah Jakarta, particularly in creating an educational climate that supports character development, discipline, and quality of learning. This study uses a qualitative approach with a case study type. Data were collected through in-depth interviews with the principal, teachers, administrative staff, and students, participant observation of madrasah activities, and documentation analysis. The data obtained were analyzed using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results show that organizational culture at MTs Darunnajah Jakarta is characterized by the existence of behavioral rules, norms, and dominant values that emphasize respect, politeness, discipline, and kinship. The principal plays a central role in fostering this culture through structural strategies, such as religious programs and routine activities, as well as non-structural strategies such as role models, moral development, and democratic communication. Supporting factors for fostering organizational culture include parental involvement, teacher loyalty, and the existence of character-building programs, while inhibiting factors include limited resources and the inactivity of some teachers and students. These findings emphasize the importance of visionary, transformational, and participatory leadership in building a productive and competitive organizational culture in madrasas.